ANALYSIS OF COMMENTS – HOW DIFFERENT IS MEDIA CONTENT FROM THE COMMENTS THAT FOLLOW IT? - Sedlarević, Maja (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
ABSTRACT The paper examines how and in what manner reader comments on media posts correspond with the text, as well as the content of those comments, their intended recipients, linguistic expressions used, and how they convey their stance on a particular topic/phenomenon/event and/or individual. Reader comments on media posts illustrate the extent to which the freedom they enjoy in the digital space can lead to discriminatory behavior, aggression, and various forms of verbal violence. For this reason, in this paper, we focus on the phenomenon of commenting on media content.The focus of this study is a current and pervasive phenomenon concerning audience comments on media content in the digital sphere. For the purposes of this research, comments on texts of the same topic, published on the portal and Facebook page of one media outlet, were analyzed for both 2020. and 2022. This research aims to provide an authentic portrayal of the correlation and interaction between media content and the comments that readers write underneath it.Special attention is given to the occurrence of hate speech, with a particular emphasis on sexism, discrimination against LGBT individuals, and stereotypical portrayals of the individuals being commented on. The research results indicate that the woman who were the subjects of the posts in the comments were either ignored or depicted extremely negatively.Keywords: digital sphere, interaction, comment, LGBT individuals, media content, misogyny, equality, sexism, verbal violence, women